Effects Of Unsaturated Fatty Acids On The Conformational State Of Nicotinic Acetylcholine Receptor - Perillo, Vanesa Liliana (2010)
Free fatty acids (FFA) are non-competitive antagonists of the nicotinic acetylcholine receptor (AChR) and their site of action is supposedly located at the lipid-AChR interface, where lipids can be annular or non-annular. It is known that the cis-unsaturated FFA, and not trans-unsaturated FFA, produce conformational modifications in the AChR resting state. Using T. californica receptor-rich membranes, we studied the changes in AChR conformational state generated by differences in the double-bond position of monounsaturated FFA. Using the higher affinity of the fluorescent AChR blocker crystal violet for the desensitized than for the resting state, it was observed that a double bond in positions ù 6 or ù 9 increased the KD values of the AChR in the desensitized state whereas no effect was observed in ù 11 or ù 13. Only FFAwith an ù 9 double bond changed the KD values in the resting state. DPH and Laurdan fluorescence studies showed that fluidity increased the most in FFAwith ù 9 and ù 11 double bonds and that ù 6 and ù 13 had less effect. Fluorescence resonance energy transfer experiments showed that the FFAwith an ù 6 double bond remained as an annular lipid whereas all the others also interact at non-annular sites. Thus, the location of the unsaturated double bond appears to be of critical importance for FFA-AChR interaction.